Congenital diaphragmatic hernia: 10-year evaluation of survival, extracorporeal membrane oxygenation, and foetoscopic endotracheal occlusion in four high-volume Centres - Snoek, Kitty G.; Schaible, Thomas (Neonatology, 2018)
Background: Congenital diaphragmatic hernia (CDH) is a severe congenital anomaly with significant mortality. Objectives The aim of this study was to determine if there were trends in survival over the last decade and to compare patient populations, treatment options, and survival rates between 4 high-volume centres, and hence determine which factors were associated with survival. Methods: In 4 high-volume CDH centres from the CDH EURO Consortium, data from all CDH patients born between 2004 and 2013 were analysed. The predictive value of variables known at birth and the influence of centre-specific treatments (extracorporeal membrane oxygenation, ECMO, and foetoscopic endotracheal occlusion, FETO) on survival were evaluated in multivariable logistic regression analyses. Results: Nine hundred and seventy-five patients were included in the analysis, of whom 274 (28.1%) died. ECMO was performed in 259 patients, of whom 81 (31.3%) died. One hundred and forty-five patients (14.9%) underwent FETO, and from those 76 patients (52.4%) survived. Survival differed significantly between years (p = 0.006) and between the 4 centres (p < 0.001). In the multivariable logistic regression analysis, lung-to-head ratio, gestational age at birth, ECMO, centre of birth, and year of birth were significantly associated with survival, whereas FETO was not. Conclusions: The patient populations were different between centres, which influenced outcomes. There was a significant variability in survival over time and between centres, which should be taken into consideration in the planning of future trials.